Do public media campaigns designed to increase skin cancer awareness result in increased skin excision rates? - Christopher B. Del Mar; Adèle C. Green; Diana Battistutta (Elsevier, 1997)
Abstract We report on an observational study of one city in Queensland over a 30‐month period to evaluate the effects of two public skin cancer campaigns on the excision rates of melanocytic skin lesions. The numbers of melanomas, the numbers of potentially malignant melanocytic lesions (Hutchinson's melanotic freckles and dysplastic naevi) whose excision might have benefited the patient, and the total number of melanocytic skin lesions submitted to pathology services were recorded. A total of 3221 melanocytic skin lesions were excised. More lesions were excised during summer than non‐summer periods (rate ratio 1.22, 95% CI 1.06, 1.40) and, independently, during campaign periods than non‐campaign periods (rate ratio 1.24, 95% CI 1.11, 1.37). There were 145 melanomas (4%), of which 116 were < 0.76 mm thick, and an additional 53 (2%) other potentially malignant lesions. During campaigns, proportions of neither type increased significantly, nor was there a significant reduction in excised melanoma thickness. Doctors reported more often that the reason for excision was to exclude malignancy during the campaigns, although they felt themselves to be under less pressure from patients to excise lesions. There may be considerable cost associated with primary prevention campaigns in the form of increased excision of benign skin lesions, which should be addressed in future skin cancer public awareness campaigns.